2008
DOI: 10.1103/physreve.78.025401
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of temperature equilibration in dense hydrogen

Abstract: The temperature equilibration rate between electrons and protons in dense hydrogen has been calculated with molecular dynamics simulations for temperatures between 10 and 600eV and densities between 10;{20}cm;{-3}to10;{24}cm;{-3} . Careful attention has been devoted to convergence of the simulations, including the role of semiclassical potentials. We find that for Coulomb logarithms L greater, similar1 , a model by Gericke-Murillo-Schlanges (GMS) [D. O. Gericke, Phys. Rev. E 65, 036418 (2002)] based on a T -ma… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
106
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 82 publications
(110 citation statements)
references
References 21 publications
3
106
1
Order By: Relevance
“…For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8]. Furthermore, it was shown that for many regimes of interest to ICF, the complex dynamical screening of the 2-component (electron + proton) plasma could be replaced by the static response of the electrons alone, yielding identical results [8,9,12,13]. This is hardly surprising, since in a given electronproton collision, the "spectator" electrons are expected to move much faster than the much heavier "spectator" protons.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8]. Furthermore, it was shown that for many regimes of interest to ICF, the complex dynamical screening of the 2-component (electron + proton) plasma could be replaced by the static response of the electrons alone, yielding identical results [8,9,12,13]. This is hardly surprising, since in a given electronproton collision, the "spectator" electrons are expected to move much faster than the much heavier "spectator" protons.…”
Section: Introductionmentioning
confidence: 74%
“…All but a few of these studies [7,11,14] confined themselves to pure hydrogen (or the proton-positron system [8,9]). Even for H, the demonstration of agreement between MD results and kinetic theory took some time [10][11][12][13], in part because the effect of using the QSPs changes the result slightly even in weak coupling [11]. For the classical like-charge proton-positron system, demonstration of agreement was somewhat more straightforward, motivating a clear connection between the classic LandauSpitzer equilibration rate [15] derived from the Fokker-Planck equation, and a generalized Lenard-Balescu [16] scheme in which both dynamical screening and 2-body static correlations (in the form of local field corrections) are included [8].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations